Foreign Russian Newspaper: Phenomenology of the Periodical - Gromova, Lydmila Petrovna; Tsvetova, Natalya Sergeevna (International Review of Management and Marketing, 2015)
The purpose of the article is to analyze the status of Russian discourse of the German media space in wide historical context by the example of most popular printed periodicals. The first part of the paper is historical-informative. This part suggests the following problems: when and in what countries did the first foreign Russian periodicals appear? In what forms and how long did they exist? What is the general direction of evolution of the Russian mass-media in Germany? The second part deals with the study of phenomenology of the periodical, which became the object of scientific interest, mainly by the example of the weekly publication "Russian Berlin/ Russian Germany". This section provides a view on cumulative newspaper text (the analysis of title, editorial classification, advertising remarks etc.). A topical organization of cumulative newspaper text is studied as a manifestation of ideology of the collective author, as a powerful contact-establishing instrument. A super-task of the publication, fixed in the chain of key words, presenting a complex semantic structure, is revealed. The main conclusion: modern journalistic discourse of Russian foreign countries is in decay. The layering of discourse is determined, firstly, by the degradation (in relation to tradition) of ideologically-pragmatic orientations of periodical addressers and by changed demands of the audience, resulting in the modernization of the verbal form of the media-text. Keywords: discourse, Russian world, media-sphere, cumulative newspaper text, typology, phenomenon, super-task. JEL Classifications: D83; Z10; Z13; Z19